Mediterranean-Style Diet for the Primary and Secondary Prevention of Cardiovascular Disease: A Cochrane Review. Issue 1 (12th August 2020) - Rees, Karen; Takeda, Andrea; Martin, Nicole; Ellis, Leila; Wijesekara, Dilini; Vepa, Abhinav; Das, Archik; Hartley, Louise; Stranges, Saverio
Background: Diet plays a major role in cardiovascular disease (CVD) risk. Objectives: To determine the effectiveness of a Mediterranean-style diet for the primary and secondary prevention of CVD. Methods: We searched for randomised controlled trials (RCTs) of Mediterranean-style diets in healthy adults and those at increased risk of CVD (primary prevention) and with established CVD (secondary prevention). Results: Thirty RCTs were included, 22 in primary prevention and eight in secondary prevention. Clinical endpoints were reported in two trials where there was moderate quality evidence for a reduction in strokes for primary prevention, and low quality evidence for a reduction in total and CVD mortality in secondary prevention. We found moderate quality evidence of improvement in CVD risk factors for primary prevention and low quality evidence of little or no effect in secondary prevention. Conclusions: There is still some uncertainty regarding the effects of a Mediterranean-style diet in CVD prevention.